Lockdown experience, beliefs in and practice of spirituality: Implications for health and self-protective behaviours - Biswas, Urmi Nanda (Mental health, religion & culture, 2022)
The research aims to understand the relationship between spiritual beliefs and practices with perceived general health and adherence to recommended self-protective behaviour during lockdown period of COVID 19 pandemic. Additionally, the study intends to find out the differences among socio-demographic segments of the Indian society across these variables. Online survey was carried out with 1,416 willing adult participants from different socio-demographic segments. Findings suggest that irrespective of age and faith, participants used spirituality as a method of coping. Various socio-demographic segments of the population differed in their self-protective behaviors, perceived general mental health, and practice of spirituality. Regular practice of spirituality was positively correlated with self-protective behaviors and perception of better general mental health. Findings suggest that improved understanding of behavioral responses of different socio-demographic segments under conditions of uncertainty would enhance the cultural competence of the intervention design and aid personalized care under uncertain and crisis situations like COVID-19.